From local reading to global understanding: Pre-service teachers’ global and multicultural literacy competencies in literary analysis - Joy D. Talens; Margie A. Magnaye (CV. Yudhistt Fateeh, 2026)
As educational environments become more globally interconnected and culturally diverse, developing global and multicultural literacy has become increasingly important in preparing future teachers to respond effectively to contemporary educational demands. This study explored how pre-service teachers in a higher education institution in the Philippines demonstrate global and multicultural literacy competencies in literary analysis through their written narratives, as these competencies are essential 21st-century skills that teachers are expected to develop and demonstrate before engaging in future teaching practice. Guided by a qualitative research design grounded in narrative inquiry, the study involved eight pre-service teachers selected through purposive sampling from a teacher education program. Data were gathered through written reflective narratives and analyzed using thematic analysis. The findings revealed that participants demonstrate global literacy competency by connecting literary texts to global and social issues, considering multiple perspectives, and reflecting on cultural identities, including their own. They also show multicultural literacy competence through their ability to support interpretations with evidence, engage respectfully with diverse viewpoints, and remain aware of personal biases. Furthermore, their narratives point to the value of reflective writing and classroom dialogue in shaping more critical and culturally responsive approaches to literary analysis. The study suggests that global and multicultural literacy are closely interconnected and play a meaningful role on how pre-service teachers interpret and respond to texts. These findings highlight the importance of integrating reflective and context-based practices in teacher education to better prepare future educators for diverse and globalized learning environments.